Selection of impalpable breast cancer for conservative surgery - Svastics, Egon (Radiology and oncology (Ljubljana), 1997)
Breast sparing surgical interventions have been accepted worldwide in early symptomatic cancer cases. They should be applied especially in the case of mammographically screened impalpable, invasive or noninvasive cancer. The dilemma is a follows: (1.) total axillary block-dissection or lower dissectionor sampling of lymph nodes, (2.) how wide the tumor "ball" should beremoved, and (3.) which types of ductal carcinoma in-situ (DCIS) should be handled with special attention, and when total mastectomy should be carried out. Thanks to the efficient mammographic screening, in most of our patients breast conserving operations can be carried out. We are planning to introduce the Van Nuys classificantion for ductal carcionoma in-situ (DCIS).
Keywords: Breast neoplasms; Mastectomy; Surgery